AN ANALYSIS ON LEARNING LOSS AND HOLISTIC EDUCATION - Zandroto, Amel Devina; Indriani, Siane (Universitas Pelita Harapan, 2023)
AbstractChristian education views students as an image of God. During the pandemic of COVID-19, students encountered learning loss phenomena which has become a challenge for Christian schools. Thus, this study aims to elaborate the difference between Christian perspective and secular perspective toward the “learning loss’ phenomena; how important a holistic education is to be implemented in the classroom; and to explain the role of the teacher as a facilitator to implement holistic learning in the classroom. The research method used in this study is literature review. The result showed that students as the image of God should be valued as a whole person, not only partially as viewed from secular perspectives. Christian teachers need to be equipped to see and teach their students holistically, such as planning their lessons to be ‘contextual’ and relevant for their students in order to raise awareness for tolerance, empower their talents, and conduct learning processes through loving interaction and applying holistic assessments. A recommendation for further research is to implement holistic education at primary level and elaborate the challenges faced by the teacher. Bahasa Indonesia AbstrakPendidikan Kristen melihat siswa sebagai Image of God. Selama pandemi covid-19 siswa menghadapi satu fenomena, yaitu Learning Loss, di mana terdapat penurunan dalam proses pembelajaran siswa. Oleh karena itu, tujuan dari paper ini adalah untuk menjelaskan perbedaan antara sudut pandang kekristenan dengan sudut pandang sekuler terkait fenomena “learning loss; pentingnya penerapan pendidikan holistis di dalam kelas, dan menjelaskan peran guru sebagai fasilitator dalam mengimplementasikan pendidikan holistis di dalam kelas. Penelitian ini dilakukan menggunakan metode kajian literatur. Hasil penelitian menunjukkan bahwa murid sebagai Image of God seharusnya dididik sebagai manusia yang utuh, dan tidak hanya sebagian seperti halnya dalam pandangan sekuler. Guru Kristen harus diperlengkapi agar dapat melihat dan mengajar secara holistik. Misalnya, merencanakan pembelajaran yang kontekstual dan relevan untuk siswa agar dapat membangkitkan kesadaran mereka akan toleransi dan mengembangkan talenta mereka. Serta mengimplementasikan pendidikan holistik di dalam kelas melalui interaksi yang didasarkan pada kasih serta penerapan penilaian holistik kepada siswa. Sebagai rekomendasi, peneliti menyarankan agar penelitian selanjutnya berfokus pada penerapan pendidikan holistik kepada murid di Sekolah Dasar serta memaparkan tantangan-tantangan yang dihadapi oleh Guru.